A practicum report at Davao Milk Processing Plant in Malagos, Baguio District, Davao City - Tolentino, Lorenz Flordalyn Alcala (2006)
The proponent had her internship at Davao Milk Processing Plant (DMPP), which started October 17, 2005 and ended on December 8 of the same year. The plant processes different milk products, which include flavored milk, sterilized milk, milk bars, white cheese and pastillas de leche. She was exposed to the different plant departments and tried different jobs as required per section. In the laboratory department, she was tasked to perform laboratory experiments for the quality testing of the raw materials and the products. She was able to conduct physic-chemical analysis and microbiological examinations. As part of her research and development project, she also performed product developments together with the plant?s quality control officer. She compared different raw materials for chocolate and mango flavored milk products and conducted sensory evaluations for product testing. She was also exposed to the raw materials department where she prepared packaging materials to be used in the processing line. As a part of her job in the processing department, she was tasked to process and bottle flavored milk products as well as help in the preparation of white cheese and pastillas de leche. In her one and a half month of plant exposure, she acquired knowledge primarily about the nature of milk and its processing techniques, as well as developed her working skills. She was also able to provide a technical analysis on plant-related factors and has given recommendations to improve plant operations